Analisis Pengaruh Profitabilitas, Likuiditas dan Leverage terhadap Nilai Perusahaan dengan Moderasi Corporate Social Responsibility - Liza Novietta; Ruswan Nurmadi; Yani Suryani; Desi Ika; Rizki Fillhayati Rambe (Journal of Trends Economics and Accounting Research, 2022)
The increasing number of researchs on firm value proves that firm value is a very important thing that must be the main concern of the firm. Companies with good firm values ​​will help the firm in achieving firm goals. Companies that are members of the manufacturing industry listed on the Indonesia Stock Exchange consist of various types of companies, all of which are of course very concerned with the value of the firm, to achieve firm goals. The manufacturing sector itself, where most of it is the main producer of the people's needs, makes the manufacturing sector in Indonesia stretch, including stable and has very good growth prospects going forward. The results of this research state that Profitability (ROA) significantly affects Firm Value (PBV), Liquidity (CR) does not significantly affect Firm Value (PBV), Leverage (DER) does not significantly affect Firm Value (PBV), Corporate Social Responsibility ( CSR) can significantly moderate the effect of Profitability (ROA) on Firm Value (PBV), Corporate Social Responsibility (CSR) can significantly moderate the effect of Liquidity (CR) on Firm Value (PBV), Corporate Social Responsibility (CSR) cannot moderate significantly the effect of Leverage (DER) on Firm Value (PBV). This research recommends that in the future, relevant research uses different research objects and different research variables, which are expected to influence firm value, to add to the literature on the importance of firm value